Levodropropizine for cough treatment in adults: a randomized controlled trial - Alifer, Olha (Psychosomatic Medicine and General Practice, 2018)
Background. A cough is one of the most frequent cause for seeking treatment. It is often associated with a substantial decrease in quality of life. Levodropropizine is a cough suppressant, that can be prescribed for this condition. In current trial was evaluated levodropropizine effectiveness in improving quality of life in adults with a cough. Methods. The study had a design of a randomized controlled trial. Adult patients (n=60) were randomized into 2 groups to receive levodropropizine or plantain syrup, a phytotherapy medication. Quality of life was evaluated with an SF-36 scale at baseline and after 7 days of treatment. Additionally, patients’ overall health status was assessed with Health, Activity and Mood Scale at pointed above time frames. Results. After the treatment, it was found a statistically significant improvement in QOL physical component in levodropropizine group compared to control group (